Additive effects of fatty acid mixtures on the levels and ratio of amyloid β40/42 peptides differ from the effects of individual fatty acids - Amtul, Zareen; Uhrig, Markus; Beyreuther, Konrad (Journal of neuroscience research, 2011)
Several studies have shown the protective and/or deleterious effects of dietary enrichment of single fatty acids (FAs) in several animal and cell-culture models of Alzheimer's disease (AD). However, potential interactions among dietary fatty acids are traditionally ignored. None of these studies has examined and compared the differential effects of FAs in combination, as well as alone, for their effects on amyloid β production or AD. Here we investigated the effects of omega-9 (oleic acid) and omega-6 (linoleic and arachidonic acids) fatty acids, either alone or combined, on Aβ production by APP-695 and SP-C99 transfected COS-7 cells. Overall, our results are the first to demonstrate that mixtures of FAs alter the production of Aβ40 and Aβ42 peptides and consequently the Aβ40:42 ratio differently from individual FAs. Here we show that the effects of a single lipid on Aβ production are not attributed to that single FA alone. Rather, the overall lipid composition influences the specificity and level of the regulated intramembranous proteolysis of APP by the γ-secretase complex. Our results reinforce the importance of studying composite lipids/nutrients rather than single lipids or nutrients.